High False-Positive Rate of (1, 3)-β-D-Glucan in Onco-Hematological Patients Receiving Immunoglobulins and Therapeutic Antibodies. (6th January 2022) - Tschopp, Jonathan; Brunel, Anne Sophie; Spertini, Olivier; Croxatto, Anthony; Lamoth, Frederic; Bochud, Pierre Yves
Abstract: Immunoglobulins and/or therapeutic antibody preparations are associated with a high rate of false-positive (1, 3)-β-D-glucan (BDG) tests in onco-hematological patients routinely screened for fungal infections. The benefit of BDG monitoring shall be balanced against the risk of false-positive tests leading to unnecessary investigations and costs in this population.